2009
DOI: 10.1111/j.1364-3703.2008.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of novel virulence activities of the Xanthomonas type III effectors AvrBs1, AvrBs3 and AvrBs4

Abstract: Xanthomonas campestris pv. vesicatoria secretes at least 20 effector proteins through the type III secretion system directly into plant cells. In this study, we uncovered virulence activities of the effector proteins AvrBs1, AvrBs3 and AvrBs4 using Agrobacterium-mediated transient expression of the corresponding genes in Nicotiana benthamiana, followed by microscopic analyses. We showed that, in addition to the nuclear-localized AvrBs3, the effector AvrBs1, which localizes to the plant cell cytoplasm, also ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…Accordingly, sweet orange genes associated with ribosome biogenesis, cell division, and growth were rapidly and strongly up-regulated by X. citri (Cernadas et al, 2008). Moreover, it has been shown that the nucleoli of Nicotiana benthamiana cells expressing AvrBs3, a homolog of PthA4, were considerably enlarged and showed nucleolar vacuoles, indicating an increased need for ribosomes in these cells (Gürlebeck et al, 2009). Therefore, considering that PthA4 is required to induce tumors in sweet orange leaves and that depletion of CsMAF1 in X. citri-infiltrated tissues correlates with canker formation and the presence of PthA4, we postulate that PthA4 might prevent the interaction of CsMAF1 with the citrus RNA Pol III complex.…”
Section: Discussionmentioning
confidence: 90%
“…Accordingly, sweet orange genes associated with ribosome biogenesis, cell division, and growth were rapidly and strongly up-regulated by X. citri (Cernadas et al, 2008). Moreover, it has been shown that the nucleoli of Nicotiana benthamiana cells expressing AvrBs3, a homolog of PthA4, were considerably enlarged and showed nucleolar vacuoles, indicating an increased need for ribosomes in these cells (Gürlebeck et al, 2009). Therefore, considering that PthA4 is required to induce tumors in sweet orange leaves and that depletion of CsMAF1 in X. citri-infiltrated tissues correlates with canker formation and the presence of PthA4, we postulate that PthA4 might prevent the interaction of CsMAF1 with the citrus RNA Pol III complex.…”
Section: Discussionmentioning
confidence: 90%
“…Ectopic expression of numerous bacterial Type III secretion system effectors (Kjemtrup et al, 2000;Cunnac et al, 2009;Gurlebeck et al, 2009) and P. infestans Crinklers Haas et al, 2009) is known to alter host immunity, resulting in tissue necrosis, browning, and chlorosis. In Pseudomonas syringae, 14 TTSS effectors elicit cell death when expressed in N. benthamiana or Nicotiana tabacum (Cunnac et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of effector genes in plant cells often leads to macroscopic phenotypes such as cell death, chlorosis, and tissue browning when expressed in host cells (Kjemtrup et al, 2000;Torto et al, 2003;Cunnac et al, 2009;Gurlebeck et al, 2009;Haas et al, 2009). To identify PexRD genes that induce phenotypic symptoms in plants, we individually inoculated the A. tumefaciens strains carrying the 62 pGR106-PexRD plasmids on N. benthamiana using both the wounding (toothpick) and agroinfiltration assays Bos et al, 2009).…”
Section: Pexrd2 Induces a Weak Cell Death Response In N Benthamianamentioning
confidence: 99%
“…Micrographs were taken with an slow-scan charge-coupleddevice SM-1k-120 camera (TRS). For the analysis of OMV formation in planta, infected plant tissue was analyzed as described previously (43).…”
Section: Methodsmentioning
confidence: 99%